The prison boom, local interpersonal violence, and domestic violence homicide - Sims, Kaitlyn M. (Journal of crime and justice, 2025)
The US prison system has exploded since 1970, dramatically reshaping social, political, and economic life in rural communities. Since 2000, roughly one in five rural Americans resides in a prison town. The prison boom is the largest public works project perhaps since the New Deal. Despite a growing interest in prison building, there is a dearth of research examining prison impact – the economic, political, and social costs and benefits for communities that result from building a prison. In this paper, we fill this gap by studying the relationship between prison impact – measured as binary prison presence and cumulative prison count – on violent crime, specifically, intimate partner and domestic violence homicide (IPV/DV). We explore the theoretical foundations for this relationship, including the economic, geographic, and social effects of prisons and correction officers as a high-risk group for perpetrating IPV/DV. Contrary to conventional wisdom, we find evidence of a negative association between prison impact and IPV/DV homicide, with an additional prison in the county corresponding with 0.04–0.12 fewer homicide events. While we are not advocating for prison building as a violence nor crime reduction strategy for communities, our findings complicate the policy consequences of the prison boom, especially in rural communities.